THE IMPACT OF FINANCIAL TECHNOLOGY ON MSME FINANCING ACCESSIBILITY: AN EMPIRICAL STUDY IN TANGERANG REGENCY - Syarkani, Yofy (AKSELERASI: Jurnal Ilmiah Nasional, 2025)
The rapid advancement of financial technology (FinTech) has transformed the landscape of micro, small, and medium enterprise (MSME) financing, particularly in emerging economies. Despite this growth, many MSMEs continue to face significant barriers in accessing formal financial services. This study conducts a structured literature review to explore the impact of FinTech on MSME financing accessibility, with a specific focus on Tangerang Regency, Indonesia. Utilizing peer-reviewed journal articles and empirical studies from global and regional contexts, the analysis identifies key mechanisms through which digital financial platforms facilitate credit access for underserved businesses. The findings reveal that FinTech enhances financial inclusion through alternative credit scoring, peer-to-peer lending, and mobile-based financial services. However, challenges such as digital literacy, regulatory uncertainty, and infrastructure limitations persist, particularly in semi-urban areas. The review also highlights that while FinTech reduces transaction costs and simplifies loan application processes, it does not fully eliminate systemic barriers for all MSMEs. By synthesizing current academic perspectives, the study offers insights into how local governments and FinTech providers can align strategies to improve financing equity. The results contribute to a nuanced understanding of the FinTech-MSME nexus in localized contexts. This paper thus serves as a foundational reference for policy development and future empirical research targeting inclusive financial ecosystems.